Association of anticoagulant therapy dosing with laboratory biomarkers and clinical outcomes in critically ill COVID-19 patients in the ICU - Vasković, Igor; Marković, Marija; Arsenović, Ljiljana; Ignjatović, Aleksandra; Stojić, Mihailo; Nešković, Vojislava (Vojnosanitetski pregled, 2026)
Background/Aim. In immunothrombotic disorders such as coronavirus disease 2019 (COVID-19), D-dimer levels are frequently elevated, reflecting increased fibrin formation and turnover. Additional biomarkers, such as the neutrophil-to-lymphocyte ratio (NLR) and levels of C-reactive protein (CRP), and lactate dehydrogenase (LDH), are associated with disease severity and outcomes. The aim of the study was to evaluate the impact of two different anticoagulation protocols on serum levels of biomarkers D-dimer, NLR, CRP, and LDH, as well as their prognostic value regarding clinical outcomes in critically ill patients with COVID-19. Methods. The retrospective study included critically ill COVID-19 patients, admitted to the Intensive Care Unit (ICU) between April 2020 and December 2021, and compared D-dimer–guided and anti-Xa–guided anticoagulation protocols. Patients were divided into two groups according to the anticoagulant therapy regimen: a group with a protocol guided by anti-Xa values (AXa group – A-XaG) and a group with a protocol dosing according to D-dimer values (D-d group – D-dG). Results. A total of 395 patients were analyzed: 137 in A-XaG and 258 in D-dG. The levels of CRP, LDH, and D-dimer were significantly lower in A-XaG compared to D-dG (p < 0.001, p < 0.001, and p = 0.001, respectively). The univariate analysis identified age [odds ratio (OR): 1.064; p < 0.001], LDH (OR: 1.002; p < 0.001), CRP (OR: 1.005; p < 0.001), and D-dimer (OR: 1.054; p = 0.020) as prognostic factors for mortality. The multivariate model analysis revealed that only age > 64 years (OR: 10.215; p < 0.001) and LDH > 395 U/L (OR: 5.491; p = 0.005) remained independently associated with mortality. Conclusion. Anti-Xa–guided anticoagulation was associated with lower inflammatory biomarker levels in ICU COVID-19 patients. While univariate analysis identified age, LDH, CRP, and D-dimer as potential prognostic factors for mortality, only age and LDH remained significant in multivariate modelling, suggesting independent prognostic value in this patient population.